THE IMPACT OF ICT-BASED INTERACTIVE STRATEGY ON SENIOR HIGH SCHOOL (SMA) STUDENTS’ SPEAKING SKILLS IN PEKANBARU INDONESIA - Rizka Maulidya; Jamilah Jamilah (Premise: Journal of English Education and Applied Linguistics, 2026)
Traditional teaching methods often provide limited opportunities for meaningful oral interaction; therefore, integrating ICT-based interactive strategies is expected to create more student-centered and communicative learning environments. This study aimed to investigate the effect of ICT-based interactive strategies on senior high school students’ speaking performance. A quasi-experimental design was employed involving an experimental and a control group at SMA Negeri 12 Pekanbaru, Indonesia, with a total of 40 students. The experimental group received instruction using ICT-based interactive strategies, while the control group was taught using conventional methods. Data were collected through speaking performance tests administered as pre-tests and post-tests and analyzed using IBM SPSS Statistics version 25, including descriptive statistics and ANOVA. The results showed a statistically significant improvement in students’ speaking performance over time (F(3,76) = 74.758, p < .05), with a large effect size (η² = 0.747). However, no significant difference was found between the post-test scores of the experimental and control groups, indicating that both instructional approaches contributed to students’ speaking development. In conclusion, ICT-based interactive strategies can support the improvement of students’ speaking skills by enhancing engagement and interaction. However, their effectiveness depends on pedagogical implementation rather than technology alone. Therefore, teachers are encouraged to integrate ICT meaningfully to create more interactive learning environments.